Evaluasi Beban Kerja Mental Operator Assembly Line OPP Window Menggunakan Metode NASA-TLX di Industri Elektronik - Sarah Awallia; Muhamad Engkos Kosim; Rini Siskayanti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Human resources play an important role in achieving organizational productivity and production targets. PT XYZ is an electronics manufacturing company producing Air Conditioners (ACs) and Dehumidifiers. In the assembly process, operators perform manual tasks assisted by a conveyor system, requiring high speed and accuracy to meet a production target of 400 units per hour. These conditions may increase operators' mental workload. This study aimed to determine the level of mental workload and identify its dominant dimensions among operators in the OPP Window Group 2 assembly line at PT XYZ. The study employed the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method involving 29 operators. Data were analyzed using NASA-TLX, reliability testing, and Pareto analysis. The reliability test produced a Cronbach's Alpha value of 0.797, indicating that the instrument was reliable. The average NASA-TLX score was 80.69, indicating a very high mental workload. Seventeen operators were classified as very high, nine as high, and three as moderately high. Pareto analysis identified Own Performance, Effort, Temporal Demand, Physical Demand, and Frustration Level as the dominant dimensions, contributing 86.35% cumulatively. The findings indicate that assembly operators experience a very high mental workload, mainly influenced by performance pressure, work effort, time pressure, physical demands, and frustration.